PENGGUNAAN APLIKASI SCHOOLOGY PADA SMARTPHONE UNTUK MENINGKATKAN MINAT BELAJAR KIMIA SISWA SMA PUSAKA 1 JAKARTA - Nova Irawati Simatupang; Fenny Maria; Elferida Sormin (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
his research aims to: (1) to find out whether there is an increase in students' interest in learning chemistry through the use of Schoology applications. (2) to find out how much increased interest in learning chemistry students through the use of Schoology applications. The type of research used is the quantitative description. Sampling technique, namely purposive sampling, the sample divided into two classes, namely the control class 38 students and the experimental class 38 students. The innovative course taught using a guided inquiry learning model utilizing application Schoology, while the control class uses a guided inquiry learning model without the application. The research instrument in the form of a questionnaire the scale of measurement using a Likert scale. Hypothesis testing using a paired sample t test with a significance of 0.05 obtained the results of tcount (5.561) > ttable (2.377) and significant value of 0.00 < 0.05. Based on data analysis and hypothesis testing assisted by SPSS for Windows Version 22.0, that there was an increase in students' interest in learning chemistry through the use of Schoology applications. To find out how much increased interest in students learning through the use of application Schoology by using the gain test results obtained at 35.5% in the medium category.